2010
DOI: 10.1080/15287394.2010.511551
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cyclooxygenase-2 by 4-Nonylphenol is Mediated Through the Cyclic Amp Response Element Activation Pathway

Abstract: The organic compound nonylphenol (NP) belongs to the family of alkylphenols and is a product of industrial synthesis formed during phenol alkylation. Nonylphenol is considered to be an endocrine disruptor due to weak ability to mimic estrogen and subsequently to disrupt the natural balance of hormones in a given organism. Since the endocrine and immune systems share portions of common signaling pathways, it is conceivable that NP may also affect immune system functions. However, the influence of NP on inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Consistent with the COX‐2 expression, PGE2 as a result of COX‐2 activity also increased in NP‐challenged TM4 cells. The similar results were found in NP‐stimulated RAW264.7 cells (Han et al, ) and mouse brain (Zhang et al, ). IL‐6 is a pleiotropic cytokine produced by a variety of cell types.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the COX‐2 expression, PGE2 as a result of COX‐2 activity also increased in NP‐challenged TM4 cells. The similar results were found in NP‐stimulated RAW264.7 cells (Han et al, ) and mouse brain (Zhang et al, ). IL‐6 is a pleiotropic cytokine produced by a variety of cell types.…”
Section: Discussionsupporting
confidence: 83%
“…28 NP also activated phosphatidylinositol 3 (PI3)-kinase, Akt, p38 kinase, JNK, and the phosphorylation of cyclic AMP response element binding protein (CREB) in macrophages. 29 In addition, it altered the activities of plasma membrane Ca 21 -ATPase, Ca 21 /Mg 21 -ATPase, and Na 1 /K 1 -ATPase in Sertoli cells. 30 NP was also shown to inhibit NF-jB transactivation in murine macrophages activated with LPS.…”
Section: Discussionmentioning
confidence: 96%
“…One study revealed that NP activated neutrophils through the activation of protein kinase C, p38 kinase, and ERK . NP also activated phosphatidylinositol 3 (PI3)‐kinase, Akt, p38 kinase, JNK, and the phosphorylation of cyclic AMP response element binding protein (CREB) in macrophages . In addition, it altered the activities of plasma membrane Ca 2+ ‐ATPase, Ca 2+ /Mg 2+ ‐ATPase, and Na + /K + ‐ATPase in Sertoli cells .…”
Section: Discussionmentioning
confidence: 99%
“…Activated immune cells like macrophages would generate ROS. Indeed, Han et al [42] showed that inflammatory responses were induced by NP in murine macrophage RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 98%